2013
DOI: 10.4103/0019-5154.110838
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of leishmanin skin test reaction in different variants of cutaneous leishmaniasis

Abstract: Introduction:Cutaneous leishmaniasis (CL) is a parasitic disease which has different clinical forms. The aim of this study is to compare the response to leishmanin skin test (LST) in three forms of CL including plaque type, lupoid type, and sporotrichoid type.Materials and Methods:This was a descriptive cross-sectional study. The patients enrolled in this study had three clinical forms of CL confirmed by positive smear of their lesions and then LST was performed for them. Results were categorized as negative (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…LST provokes this immune response by reintroducing Leishmania antigens into the skin with a positive result being interpreted as a sign of previous infection by the Leishmania parasite; the test has been used as a diagnostic tool for leishmaniasis for the past 50 years . Based on current evidence, LST conversion following infection occurs within few days to a few months . The test has acceptable sensitivity and very high specificity (85% and 100%, respectively) and thus a positive result can be interpreted as previous exposure to the parasite with very high accuracy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LST provokes this immune response by reintroducing Leishmania antigens into the skin with a positive result being interpreted as a sign of previous infection by the Leishmania parasite; the test has been used as a diagnostic tool for leishmaniasis for the past 50 years . Based on current evidence, LST conversion following infection occurs within few days to a few months . The test has acceptable sensitivity and very high specificity (85% and 100%, respectively) and thus a positive result can be interpreted as previous exposure to the parasite with very high accuracy .…”
Section: Discussionmentioning
confidence: 99%
“…9 Based on current evidence, LST conversion following infection occurs within few days to a few months. 10 The test has acceptable sensitivity and very high specificity (85% and 100%, respectively) and thus a positive result can be interpreted as previous exposure to the parasite with very high accuracy. 4,11 Furthermore, the immune response mechanism of the test has been previously inferred as resistance towards reinfection by Leishmania parasites; this assumption has formed the basis of vaccine development efforts thus far, which have aimed to render individuals LST positive.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used leishmanin skin test (LST), which is a classical delayed hypersensitivity test, where parasite antigen is injected intradermally and responses in terms of tissue swelling and inflammation is determined after a few days. Self‐healing lesions are associated with antigen‐specific T‐cell responses and a positive LST reaction . T cells from patients with MCL are hyperresponsive to antigenic stimulation and LTS reactions large, reflecting on an aggressive effector T‐cell response , while patient with DCL fail to generate antigen‐specific response and often are LST negative .…”
Section: Cell‐mediated Immunity Determines Clinical Outcome In CLmentioning
confidence: 99%
“…The factors that trigger lymphatic dissemination are unclear but some data suggest that the host immune status could influence this dissemination [10,11]. Indeed, Sadeghian et al [20] showed that the leishmanin skin test (LST) was negative in 72% of SF cases and that none was strongly positive in LST positive patients. They concluded that the SF of CL is at least partially due to a decrease in cellular immunity.…”
Section: Discussionmentioning
confidence: 99%